The Influence of Islamic Financing on Profitability of Sharia Commercial Banks in Indonesia - Muhammad Fachrizal Wahyu Darma Putra; Fitrian Aprilianto; Afifah Nur Millatina (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The aims of this study to analyze this is to analyze the effect of murabahah financing, musyarakah financing, mudharabah financing and ijarah financing on the profitability (ROA) of Islamic commercial banks for the period 2015-2021. The type of research used is a type of quantitative research with an associative approach. The dependent variable used in this study is profitability (ROA). The results of this study indicate that; murabahah financing partially has a negative and insignificant effect on the profitability (ROA) of Islamic commercial banks, musyarakah financing partially has a positive and significant effect on the profitability (ROA) of Islamic commercial banks, mudharabah financing partially has a negative and insignificant effect on the profitability (ROA) of banks general sharia, ijarah financing partially has a positive and significant effect on the profitability (ROA) of Islamic commercial banks. Murabahah financing, musyarakah financing, mudharabah financing and ijarah financing simultaneously have a significant effect on the profitability (ROA) of Islamic Commercial Banks.